Preferensi Wisatawan Terhadap Butler Service Signature di The ST. Regis Bali Resort - Ni Nyoman Suci Arthini; Ni Kadek Windi Karlina Dewi; Ni Ketut Sekarti (Program Studi Manajemen Divisi Kamar, 2022)
This study aims to determine the preferences of tourists to the butler service signature at Hotel X. Hotel X applies three types of butler services, namely semi butler, 12-hour private butler service, and 24-hour private butler service. The data collection technique used is the documentation technique using a sample of 30 reviews of tourists who stay at Hotel X. The data analysis technique used is descriptive qualitative and analyzed using five aspects of guest preferences including, packing & unpacking service, pressing service, e-butler, beverage service and butler service desk. The results showed that most tourists were satisfied with all aspects of the five butler signatures such as packing & unpacking, pressing service, e-butler, beverage service and butler service desk. So expect Hotel X always evaluates the implementation of butler service and improves services comprehensively to staying tourists.